2023
DOI: 10.3389/fcvm.2023.1220095
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating diabetes-associated atherosclerosis and diabetic nephropathy through modulation of soluble guanylate cyclase

Abstract: Diabetes mellitus (DM) is an independent risk factor for micro- and macrovascular complications such as nephropathy and atherosclerosis respectively, which are the major causes of premature morbidity and mortality in Type 1 and Type 2 diabetic patients. Endothelial dysfunction is the critical first step of vascular disease and is characterized by reduced bioavailability of the essential endothelial vasodilator, nitric oxide (NO), coupled with an elevation in inflammation and oxidative stress. A novel pathway t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…A study revealed that soluble guanylate cyclase activator cinaciguat treatment restored the glomerular cGMP content and soluble guanylate cyclase expression, improved diabetes-induced glomerular damage, apoptosis, podocyte injury, proteinuria, and TIMP-1 overexpression by suppressing TGF-β and ERK1/2 signaling [48]. Furthermore, additional studies also demonstrated the renoprotective effects of a guanylate cyclase activator or stimulator through increasing cGMP via the NO-soluble guanylate cyclase pathway [47,[319][320][321][322][323][324]. A RCT revealed that PF-00489791, an inhibitor of cGMP-hydrolyzing enzyme phosphodiesterase type 5 (PDE5), had been found to effectively reduce albuminuria in patients with overt diabetic nephropathy [274].…”
Section: Other Novel Antioxidative Therapiesmentioning
confidence: 98%
See 3 more Smart Citations
“…A study revealed that soluble guanylate cyclase activator cinaciguat treatment restored the glomerular cGMP content and soluble guanylate cyclase expression, improved diabetes-induced glomerular damage, apoptosis, podocyte injury, proteinuria, and TIMP-1 overexpression by suppressing TGF-β and ERK1/2 signaling [48]. Furthermore, additional studies also demonstrated the renoprotective effects of a guanylate cyclase activator or stimulator through increasing cGMP via the NO-soluble guanylate cyclase pathway [47,[319][320][321][322][323][324]. A RCT revealed that PF-00489791, an inhibitor of cGMP-hydrolyzing enzyme phosphodiesterase type 5 (PDE5), had been found to effectively reduce albuminuria in patients with overt diabetic nephropathy [274].…”
Section: Other Novel Antioxidative Therapiesmentioning
confidence: 98%
“…Glu298Asp polymorphism in the eNOS gene has been shown to modulate NO production and has been associated with DKD [46]. Decreased soluble guanylate cyclase activity and cyclic guanosine monophosphate (cGMP) levels in diabetic kidneys were shown to influence the progression of nephropathy through modulating the protective actions of NO [47,48]. Therefore, drugs capable of restoring guanylate cyclase activity and cGMP levels could potentially offer a promising adjunctive therapeutic approach for individuals with diabetic nephropathy.…”
Section: Uncoupled Nosmentioning
confidence: 99%
See 2 more Smart Citations